Emerging disparities in community resilience to drought hazard in south-central United States - Mihunov, Volodymyr V.; Lam, Nina S. N.; Rohli, Robert V.; Zou, Lei (International Journal of Disaster Risk Reduction, 2019)
In search of new insights into the dynamics of hazard resilience, this study assessed the temporal changes of community resilience to the drought hazard in the south-central U.S. The study hypothesized that over time counties with more affluent socioeconomic conditions and more diverse agriculture would improve their resilience while counties with poorer socioeconomic conditions and heavy reliance on agriculture decreased their resilience, thus widening the regional disparities in community resilience to the drought hazard. The study applied the Resilience Inference Measurement (RIM) framework to measure the resilience levels of the 503 counties of Arkansas, Louisiana, New Mexico, Oklahoma, and Texas. Using data of Year 2000, the RIM model selected 10 variables as resilience predictors with a 67.9% classification accuracy and assigned a resilience level to each county. The variables selected in the RIM model are related to the economic performance in the agricultural sector, socioeconomic well-being, and health. The derived discriminant functions from the RIM model were then used to estimate the resilience levels in 2005, 2010, and 2015. Over the 15-year period, 262 counties across the study area improved their resilience, whereas 48 counties, mostly in the Texas High Plains, experienced a decrease in their resilience level. The results support the hypothesis and suggest a widening gap in resilience levels among counties. These results increase our understanding of the complex process underlying communities’ response to the drought impacts.
Keywords: Climatological hazard; Community resilience; Drought hazard; Resilience inference measurement (RIM) model; South-central United States; Temporal dynamics